Analysis of Methods and Equipments for Forming Small and Medium Diameter Welding Pipes (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2025)
The article examines the methods of forming small and medium-diameter pipes, provides calibration of the forming mill rolls, and analyzes the composition and purpose of the equipment of the pipe-electric welding machines. The structure and functional roles of the equipment in pipe-electric welding machines, such as forming stands, vertical stands, welding machines, seam-cooling systems, calibration stands, and finishing sections are described. Particular attention is given to the working of forming stands and their calibration, deformation forces and the importance of local heat treatment and weld seam cooling in achieving high product quality.